2021
DOI: 10.1371/journal.pone.0245894
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiologic and economic impact of a quadrivalent human papillomavirus vaccine in Thailand

Abstract: Background The human papillomavirus (HPV) vaccine was introduced into Thailand’s national immunization program in 2017 for 11–12 year old school girls. The objectives of this study were to examine the epidemiological consequences and cost-effectiveness of a routine quadrivalent HPV (4vHPV) vaccination and the routine 4vHPV vaccination plus 5-year catch-up vaccination by comparing with cervical cancer screening only (no vaccination) in Thailand. Method A transmission dynamic model was used to assess the cost-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…For Thailand, despite the coverage of both the screening and vaccination programs was beyond 60%, the incidence of cervical cancer was still high with crude incidence rate of 25.6 per 100 000 women 28 . One possibility was that the national immunization program was only introduced in 2017, 29 and the benefit of the vaccines was not yet manifested by the current data.…”
Section: Discussionmentioning
confidence: 99%
“…For Thailand, despite the coverage of both the screening and vaccination programs was beyond 60%, the incidence of cervical cancer was still high with crude incidence rate of 25.6 per 100 000 women 28 . One possibility was that the national immunization program was only introduced in 2017, 29 and the benefit of the vaccines was not yet manifested by the current data.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of nonavalent vaccine-type HPV infection was approximately two times higher than that of the bivalent vaccine-type for both school grades. A study that assessed the impact of quadrivalent HPV vaccine use in Thailand showed it to be cost-effective with or without catch-up immunization [30] . Our findings demonstrated a substantial burden of HR HPV infection that is not targeted by bivalent or quadrivalent HPV vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Thailand it was shown that if a catch-up program was implemented to vaccinate young women who were not previously vaccinated, it would cost less than 10,000 Thai Baht per Quality-of-Life Points (QUALYs). The recommended threshold for Thailand according to its government stood at 160,000 Thai Baht per QUALY proving that the implementation of a vaccination program would be cost effective ( 37 ). Therefore, it is important to consider the ultimate benefits of developing vaccination programmes for the health outcomes of the general population and the cost-effectiveness of such programmes.…”
Section: Vaccinationsmentioning
confidence: 99%